2023
DOI: 10.1007/s10997-023-09668-7
|View full text |Cite
|
Sign up to set email alerts
|

Does top management team diversity affect accounting quality? Empirical evidence from Germany

Abstract: Earnings management decisions and ineffective monitoring activities have contributed to financial accounting scandals and reduced confidence in firms’ reporting quality among potential investors, lenders and other creditors. The implementation of an effective top management team (TMT) is considered essential in this context. It is well known that top managers have considerable discretion over firms’ financial reporting since they choose whether and how to manage earnings. However, research has yet to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…However, the question of how a higher proportion of women in boards affects corporate performance is controversial and the empirical evidence is inconclusive (Reddy and Jadhav, 2019). While some authors find positive effects on firm performance (Schumann et al, 2023;Brahma et al, 2020;Adams and Ferreira, 2016;Joecks et al, 2013), others report negative (Hosny and Elgharbawy, 2022) or non-significant results (Fleischer, 2022;Rose, 2007).…”
Section: Literature Review On Board Composition and Performancementioning
confidence: 99%
See 3 more Smart Citations
“…However, the question of how a higher proportion of women in boards affects corporate performance is controversial and the empirical evidence is inconclusive (Reddy and Jadhav, 2019). While some authors find positive effects on firm performance (Schumann et al, 2023;Brahma et al, 2020;Adams and Ferreira, 2016;Joecks et al, 2013), others report negative (Hosny and Elgharbawy, 2022) or non-significant results (Fleischer, 2022;Rose, 2007).…”
Section: Literature Review On Board Composition and Performancementioning
confidence: 99%
“…Besides the demographic characteristics of age and gender, recent studies on board composition increasingly take into account the ethnic and cultural background of board members. In multinational companies, for example, it is common practice to fill board positions with people of different nationalities (Schumann et al, 2023;Harjoto et al, 2019). Cultural diversity created in this way is assumed to open up different ways of solving problems and break down rigid ways of thinking that can occur in culturally homogeneous boards (Nederveen et al, 2013).…”
Section: Literature Review On Board Composition and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Surface-level characteristics act as a stand-in for cognitive resources and personal, difficult to discern, characteristics (Jackson et al , 1995; Soleimani and Stauffer, 2022; Wang et al , 2022). For instance, research using upper echelons theory has demonstrated linkages between the demographic characteristics of a firm’s leaders and organizational decisions and outcomes (Finkelstein et al , 1996; Javed et al , 2023; Roberson and Hyeon, 2007; Schumann et al , 2023). In line with this stream of thinking, race and gender have often been used in diversity research as proxies for differences in perspectives and human capital (Hillman et al , 2002; Kolev and McNamara, 2020; Roh and Sung, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%